Phosphoinositides, Ezrin/Moesin, and rac1 Regulate Fusion of Rhodopsin Transport Carriers in Retinal Photoreceptors - Deretic, Dusanka (The American Society for Cell Biology, 2004)
The post-Golgi trafficking of rhodopsin in photoreceptor cells is mediated by rhodopsin-bearing transport carriers (RTCs) and regulated by the small GTPase rab8. In this work, we took a combined pharmacological-proteomic approach to uncover new regulators of RTC trafficking toward the specialized light-sensitive organelle, the rod outer segment (ROS). We perturbed phospholipid synthesis by activating phospholipase D with sphingosine 1-phosphate (S1P) or inhibiting phosphatidic acid phosphohydrolase by propranolol (Ppl). S1P stimulated the overall rate of membrane trafficking toward the ROS. Ppl stimulated budding of RTCs, but blocked membrane delivery to the ROS. Ppl caused accumulation of RTCs in the vicinity of the fusion sites, suggesting a defect in tethering, similar to the previously described phenotype of the rab8T22N mutant. Proteomic analysis of RTCs accumulated upon Ppl treatment showed a significant decrease in phosphatidylinositol-4,5-bisphosphate–binding proteins ezrin and/or moesin. Ppl induced redistribution of moesin, actin and the small GTPase rac1 from RTCs into the cytosol. By confocal microscopy, ezrin/moesin and rac1 colocalized with rab8 on RTCs at the sites of their fusion with the plasma membrane; however, this distribution was lost upon Ppl treatment. Our data suggest that in photoreceptors phosphatidylinositol-4,5-bisphosphate, moesin, actin, and rac1 act in concert with rab8 to regulate tethering and fusion of RTCs. Consequentially, they are necessary for rhodopsin-laden membrane delivery to the ROS, thus controlling the critical steps in the biogenesis of the light-detecting organelle.